Implementasi Metode Pakistani Dalam Pembelajaran Tahfidz Di Pondok Pesantren Darul Hijrah Wal Amanah Kota Padang (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
To achieve the desired goals in studying Tahfidz Al-Quran, the method used is crucial. The Pakistani Tahfidz method is employed at the Darul Hijrah Wal Amanah Islamic Boarding School in Padang City to teach Tahfidz Al-Quran. The Tahfidz Al-Quran program at this boarding school is implemented in a distinctive manner. The aim of this research is to describe and examine the application of the Pakistani method in Tahfidz learning at the Darul Hijrah Wal Amanah Islamic Boarding School in Padang City, including its implementation and evaluation. This study uses qualitative methods with a field research approach. Data collection techniques included interviews, observations, and documentation. The research results indicate that the implementation of the Pakistani method in Tahfidz learning has several impacts: students become more focused on memorization, develop a confident personality, and become accustomed to memorizing in front of large audiences.
Keywords: Implementation; Pakistani Method; Tahfidz Al-Quran